Synthesis, field emission and optical properties of ZnSe nanobelts, nanorods and nanocones by hydrothermal method. (March 2015) - Zeng, Q.Z.; Xue, S.L.; Wu, S.X.; Gan, K.X.; Xu, L.; Han, J.W.; Zhou, W.K.; Shi, Y.T.; Zou, R.J.
Abstract: ZnSe nanostructures, such as nanobelts, nanorods and nanocones, were successfully synthesized on Zn foils via a hydrothermal method using EDTA as soft template at low temperature. EDTA played a significant role on the morphology of ZnSe nanomaterials. X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM) and energy dispersive spectrometer (EDS) were carried out to characterize the microstructures and chemical compositions of the as-synthesized ZnSe samples. XRD patterns indicated that the as-synthesized ZnSe samples belonged to a cubic zinc blende structure. SEM observation obviously showed that the nanocones had very sharp tips compared to nanorods and nanobelts. The field emission (FE) measurement showed that the as-synthesized ZnSe nanocones had a lower turn-on field of 1.6 V μm −1 at the current density of 10 μA cm −2 . A high field enhancement factor of 4514 was achieved for the ZnSe nanocones. The superior field emission properties were probably attributed to the sharp tips of the ZnSe nanocones. Room temperature photoluminescence (PL) spectroscopy of the ZnSe nanostructures showed a wide band emission from blue light to orange light. The as-prepared ZnSe nanomaterials have promising applications in optoelectronic devices. A possible formation mechanism of ZnSe nanobelts, nanorods and nanocones was also proposed and discussed.